Zircon of Triassic Age in the Stuttgart Formation (Schilfsandstein)—Witness of Tephra Fallout in the Central European Basin and New Constraints on the Mid-Carnian Episode - Zeh, Armin; Franz, Matthias; Obst, Karsten (Frontiers in Earth Science, 2021)
The Carnian Stuttgart-Formation (Schilfsandstein) of the Central European Basin contains relics of Triassic volcanic detritus in form of euhedral zircon grains and authigenic analcime. Multiple LA-ICP-MS spot analyses of single zircon crystals from an outcrop near Heilbronn (SW Germany) yielded weighted average 206Pb/238U ages between 250 and 230 Ma, providing evidence for tephra fallout in the southern part of the Central European Basin related to Olenekian, Anisian–Ladinian and Carnian volcanic activity. The tephra probably was transported by monsoonal circulations from volcanic centres of the NW Tethys to the Central European Basin. The four youngest zircon crystals gave a weighted average 206Pb/238U age of 231.1 ± 1.6 Ma (10 analyses), which is interpreted to date syn-depositional tephra fallout into the fluvial Lower Schilfsandstein Member of the Stuttgart Formation. This new maximum depositional age provides the first evidence that deposition of the Stuttgart Formation, which represents the type-example of the mid-Carnian episode, a global episode of enhanced flux of siliciclastic detritus and related environmental perturbations, occurred during the Tuvalian 2 substage at ca. 231 Ma, about 3 million years later than suggested by previous correlations. Zircon grains with weighted average 206Pb/238U ages of 236.0 ± 1.2 Ma (n=17) and 238.6 ± 1.5 Ma (n=6) and 206Pb/238U ages between 241 ± 6 and 250 ± 3 Ma point to the presence of tephra in early Carnian to Olenekian strata of the Keuper to Buntsandstein Groups. Traces of these reworked tephra were incorporated into the Stuttgart Formation due to fluvial erosion in the southern Central European Basin and at its margins.